Properties of sugar palm/glass fibre-reinforced thermoplastic polyurethane composites - Mohd Afdzaluddin, Atiqah (2018)
Sugar palm fibres are abundantly available in Malaysia and South Asian countries. In addition to the wide availability and the ease to grow and harvest the sugar palm, the properties of its fibres, such as high wear resistance, low cost of raw material, biodegradability, environmental friendliness are certain advantages. However, despite the advantages, they also have some drawbacks, for example, high water absorbance, low thermal stability and debonding between the polymer matrix and natural fibre, which cause limitations in utilizing natural fibres for different applications. Nonetheless, such drawbacks can be overcome by several modification methods were employed to strengthen the properties of natural fibres composites i.e (1) surface modification by using of 6% alkaline, 2% silane, and combined 6% alkaline-2% silane treatment, (2) fiber treatment and the reinforcement of thermoplastic polyurethane, (3) hybridization of sugar palm (SP) with glass (G) fibre, and (4) surface modification of treated sugar palm with glass fibre reinforced TPU hybrid composites. The findings show that the mechanical, morphological and structural properties of SP fibre were 2% silane treatment were compatible with TPU matrix. The influence of SP fibre at varying loading (0-50 wt%) on the physical, mechanical and thermal properties of TPU composites were evaluated. In term of physical properties, the density, water absorption and thickness swelling increases with increasing fibre loading. Conversely, the 2% silane treated were enhanced the physical properties of SP/TPU composites. Improvement in tensile, flexural, and impact properties of composites were reported for 2 % silane treated at higher SP fiber loading. Moreover, the treated SP fiber exhibited satisfactory values of storage modulus and thermal degradation. In addition, the effect of hybridization of SP with G fibres were also investigated. Hybridization of SP/G at weight ratio (30/10, 20/20, 10/30, and 0/40) were developed by melt-mixing compounding followed by hot pressing moulding. The findings indicated that hybridization of SP with G fibres enhanced the tensile, flexural, and impact properties of hybrid composites. The thermal stability were also improved in the SP/G/TPU hybrid composites. Lastly, the fiber treatment based SP/G/TPU hybrid composites were fabricated and characterized its properties. In terms of physical properties, the obtained results showed that treated hybrid composites with combined 6% alkaline-2% silane exhibited the lower density, thickness swelling and water uptake. Mechanical properties (tensile, flexural and impact) of treated hybrid composites enhanced as compared to untreated hybrid composites. However, treated 30/10 SP/G hybrid composites showed moderate range of storage modulus, loss modulus, damping factor and good thermal stability. Thus, treated hybrid 30/10 SP/G/TPU showed better physical, mechanical and thermo mechanical properties over untreated hybrid composites and it is suitable for light weight density and structural applications which can be recommend for automotive parts.